The Effectiveness of Interactive Mathematics Learning Media Based on Discovery Learning to Improve Junior High School Students' Mathematical Problem-Solving Skills - Ivania, Novia Fidela; Mahmudi, Ali (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
ABSTRACT Mathematical problem-solving skills are an important competency in the 21st century, but it is still a challenge for junior high school students due to the low active involvement of students in the learning process and the limitations of conventional learning media that do not support critical and exploratory thinking processes. This study aims to test the effectiveness of discovery-based interactive learning media in improving the mathematical problem-solving ability of grade VIII junior high school students. This study uses a quantitative method with a one group pretest-posttest design. The subjects of the study were grade VIII students in one of the junior high schools in Yogyakarta who were selected purposively. The research instruments were in the form of mathematical problem-solving ability tests and media implementation observation sheets. Data analysis was carried out using a paired sample t-test with the help of SPSS 25. The results showed a significant increase in mathematical problem-solving ability after the use of learning media, with an average difference in pretest and posttest scores of 31.806 points and a significance value of 0.000 (p < 0.05). All mathematical problem-solving indicators improved, with the